Anomalous magnetic moment of the positronium ion - Yi Liang; Paul L McGrath; Andrzej Czarnecki (New Journal of Physics, 2014)
We determine the gyromagnetic factor of the positronium ion, a three-body system consisting of two electrons and a positron, including first relativistic corrections. We find that the g -factor is modified by a term $-0.51\left( 1 \right){{α }^{2}}$ , exceeding 15 times the ${{α }^{2}}$ correction for a free electron. We compare this effect with analogous results found previously in atomic positronium and in hydrogen-like ions.